2008
DOI: 10.1557/proc-1108-a09-02
|View full text |Cite
|
Sign up to set email alerts
|

High Performance InAlAs/InAs/InGaAs Pseudomorphic High Electron Mobility Transistors

Abstract: High electron mobility transistors (HEMTs) with a pseudomorphically strained InAs channel (InAs-PHEMTs) were fabricated, and their high frequency characteristics were estimated by measuring the S-parameters. For a VDS of 1.4 V and VGS of 0.3 V, InAs-PHEMTs showed an excellent intrinsic cut-off frequency (fT, int.) as high as 90 GHz regardless of their longer LG (0.7 μm). Since fT is known to be inversely proportional to LG to the first approximation, fT, int. of our InAs-PHEMTs may reach 630 GHz if their LG is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Hot holes are known to penetrate into the gate region over the valence band discontinuity, ÁE v , thereby deteriorating the HEMT characteristics. 10) However, this effect is considered to be small for P-HEMTs for the following reasons: (1) the ÁE v between the InAlAs and InAs layers is as large as 0.31 eV 6) as compared with that between the InAlAs and InGaAs layers and (2) the hole transit time 1 obtained from the optical response is independent of V DS at a higher V DS (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hot holes are known to penetrate into the gate region over the valence band discontinuity, ÁE v , thereby deteriorating the HEMT characteristics. 10) However, this effect is considered to be small for P-HEMTs for the following reasons: (1) the ÁE v between the InAlAs and InAs layers is as large as 0.31 eV 6) as compared with that between the InAlAs and InGaAs layers and (2) the hole transit time 1 obtained from the optical response is independent of V DS at a higher V DS (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…10) 2DEG concentration of the pseudomorphic channel in InAs-PHEMTs. 6) Clearly, the Auger mechanism dominates the recombination in InAs. Using the experimentally obtained CHSH (4:0 Â 10 À11 s), it was found that holes accumulated in the source region, and that their concentration reached as high as 2 Â 10 18 cm À3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study regarding the effect of optical irradiation on InAlAs/InGaAs HEMT characteristics, we demonstrated that a shift of threshold voltage (V TH ) in InAlAs/InGaAs HEMTs is caused by the change in the Fermi level due to the holes accumulated in the source region [3,4]. The carrier lifetime of accumulated holes is dominated by Auger recombination of holes in the two-dimensional electron gas (2DEG) [3][4][5]. Furthermore, we have shown that InAlAs/InGaAs HEMTs have a high responsivity when they are used as optical receivers [5].…”
mentioning
confidence: 99%
“…The carrier lifetime of accumulated holes is dominated by Auger recombination of holes in the two-dimensional electron gas (2DEG) [3][4][5]. Furthermore, we have shown that InAlAs/InGaAs HEMTs have a high responsivity when they are used as optical receivers [5]. Recently, we have demonstrated that InAs-PHEMTs can operate as not only high-speed transistors but as ultra-high speed optical receivers [3][4][5][6].…”
mentioning
confidence: 99%